Complete recovery from paraparesis in spinal cord compression due to extramedullary haemopoiesis in beta‐thalassaemia by emergency radiation therapy. Issue 4 (April 2014) - Ruo Redda, M. G.; Allis, S.; Reali, A.; Bartoncini, S.; Roggero, S.; Anglesio, S. M.; Piga, A.
Abstract Extramedullary haemopoiesis (EMH) is a complication commonly associated with beta‐thalassaemia intermedia; it is frequently asymptomatic but can sometimes lead to symptomatic tumour‐like masses. No guidelines or common consensus are available in literature regarding the different treatment strategies and only single cases have been reported. We describe a case of spinal cord compression due to intrathoracic EMH masses treated with combined radiotherapy and hydroxyurea.